Using the Allen Brain Cell Atlas of the Human Brain to Gain Insights into C-Terminal-Binding Protein 1 (CtBP1)’s Potential Function - Suhjin Lee; Uthayashanker R. Ezekiel (Biologics, 2025)
C-terminal-binding proteins (CtBPs) dimerize and function predominantly as transcriptional corepressors by recruiting various chromatin-modifying factors to promoter-bound repressors. Hypotonia, ataxia, developmental delay, and tooth enamel defects syndrome (HADDTS) is a recently discovered neurodevelopmental disorder resulting from a heterozygous missense mutation in CTBP1. It is often associated with the early onset of profound cerebellar atrophy in patients. Allen Institute’s Allen Brain Cell (ABC) atlas of human brain data was used to localize CTBP1 expression in the brain to elucidate the etiology of HADDTS. Based on the ABC atlas, CTBP1 is highly expressed in the upper rhombic lip supercluster, which gives rise to cerebellar cells and provides insights into the cerebellar pathophysiology observed in HADDTS patients.